Generációm emléktára – Orvostanhallgatók voltunk Debrecenben 1951–1957 - Fegyveres, Mária (Gerundium, 2016)
The Memorial Board of my Generation – We were Students of Medicine in Debrecen, 1951–1957. The author, who is a retired doctor of pediatric, gives us an insight into the everyday life of the students of Debrecen’s University of Medicine in the 1950s. Besides autobiographical references short anecdotes pertaining to the one-time famous professors are offered.